Intravesical onabotulinumtoxinA injections in patients on antiplatelet and anticoagulation therapy. Issue 7 (5th August 2021) - Mensah, Elsie E.; Toia, Bogdan; Nguyen, Linh; Hamid, Rizwan; Pakzad, Mahreen; Ockrim, Jeremy L.; Walker, Roger; Greenwell, Tamsin J.; Nitkunan, Tharani; Sharma, Davendra; Seth, Jai H.
Abstract: Aims: To determine the bleeding risk in patients taking anticoagulants (AC) and antiplatelets (AP) before onabotulinumtoxinA (BoNT‐A) injections and improve peri‐operative decision making and counseling. Methods: We performed a retrospective review of patients having intravesical BoNT‐A in three teaching hospitals from January 2016 to July 2018. Demographic data, indication for intravesical BoNT‐A injection, and side‐effects of significant bleeding requiring intervention were recorded. Results: Five hundred and thirty‐two patients had intravesical BoNT‐A injections during this time. Sixty‐three patients of mean age 69 years (range 19–89) had a total of 114 separate rounds of BoNT‐A injections whilst on treatment dose AC/AP therapy. Of the 63, there were 33 males, with 46 having idiopatic detrusor overactivity and 17 with neurogenic detrusor overactivity. Each patient had between 1 and 7 repeat injections during the studied period. AC/AP use across the 114 episodes included; aspirin 44, clopidogrel 37, warfarin 19, and NOAC (novel/non‐vitamin K oral anticoagulant) 14. Patients on warfarin who had point of care testing all had international normalized ratio less than 3. BoNT‐A dose varied from 100U to 300U—modal dosage was 200U.1/114(0.88%) injection episodes resulted in postinjection hematuria requiring overnight admission. This resolved spontaneously, with an overnight catheter. This patient was on rivaroxaban and had 300U of BoNT‐A injected through 20 sites, on a background of previous prostate radiotherapy and self‐catheterization. Conclusions: Continuation of AP/AC therapy during intravesical BoNT‐A injection treatment appears to be safe—with a 0.88% rate of spontaneously resolving hematuria.